Post fire succession in Tegal Panjang Grassland, Mount Papandayan, West Java, Indonesia - ENDAH SULISTYAWATI; SYLVANITA FITRIANA (Biodiversitas Journal of Biological Diversity, 2017)
Sulistyawati E, Fitriana S. 2017. Post fire succession in Tegal Panjang Grassland, Mount Papandayan, West Java, Indonesia. Biodiversitas 18: 1226-1233. Tegal Panjang is a grassland area surrounded by rainforest consisting of vegetation patches formed by fires occurring at different times. This condition presents a unique environmental setting allowing the study of vegetation succession after fire disturbance. The objectives of this research were (i) to determine the pattern of vegetative development and changes in environment conditions in post-fire grassland on five sites having different ages (6 months, 1 year, 2 years, 5 years and more than 10 year) and (ii) to examine whether post-fire succession in grassland allows the establishment of tree seedling. Measurements were conducted for vegetation composition, aboveground biomass and edaphic factors (soil pH, water content, bulk density and organic content) in each site. The pattern of vegetation development in the course of succession in Tegal Panjang grassland is marked by increasing biomass and height of the vegetation as the stand ages but with a slow rate of species diversification. No tree saplings were found in all sites despite its close distance to the forest. Recruitment limitation associated with repeated fire disturbance may explain the absence of tree saplings in the grassland.